Effect of Load Vector Orientation on Uniaxial Compressive Strength of 3D Photoresin - Evgenii Kozhevnikov; Mikhail Turbakov; Evgenii Riabokon; Zakhar Ivanov; Andrei Golosov; Arina Panteleeva; Yan Savitsky (Journal of Manufacturing and Materials Processing)
Rapid prototyping has a wide range of applications across various fields, both in industry and for private use. It enables the production of individual parts in a short time, independent of supply chains, which is particularly important in remote locations. Among all 3D printing technologies, stereolithography using photo resins is the most accessible and offers the highest printing quality. However, the strength properties of parts made from photo resins remain a critical concern. In this study, we conducted experimental research to investigate the effect of load vector orientation under uniaxial compression on the elastic and mechanical properties of 3D-printed cylindrical samples. The results revealed that samples with layers oriented at 60° to the load vector exhibited the highest strength, while those with layers at 30° to the load vector showed the lowest strength. Samples with layers aligned parallel or perpendicular to the load vector demonstrated similar strength properties. Under quasi-elastic loading, samples with layers parallel to the load vector exhibited the highest Young’s modulus and the lowest Poisson’s ratio. Conversely, samples with layers oriented at 30° to the load vector displayed the highest Poisson’s ratio. Microstructural analysis revealed that the anisotropy in the mechanical properties of the 3D-printed samples is attributed to the layered, heterogeneous structure of the photoresin, which exhibits varying degrees of polymerization along the printing axes. The upper part of each layer, with a lower degree of polymerization, contributes to the ductile behavior of the samples under shear stresses. In contrast, the lower part of the layer, with a higher degree of polymerization, leads to brittle behavior in the samples.